Tuck-'n'-roll : Rollerblade / Muhammad Haziq Abdul Malik ... [et al.] - Abdul Malik, Muhammad Haziq; Jamsari, Mohammad Faris; Kamarul Bahrain, Muhaimin; Mazlan, Muhammad Amir Fariduddin; Razman, Muhammad Rafiq Arif (2018)
Tuck-'n'-Roll is one of the rental services of roller blades. Located in the middle city of Johor Bahru that allows the entire family or young people to have satisfied their interest and try a new things in one convenient location, Hutan Bandar. Our services serves for men, women, and children of all ages and accepts appointments as well as walk-ins. In addition, Tuck-'n' Roll also sells retail roller blades products, such as K2 and Rollerblades. And extra services for maintenance and coaching. Our business crews able to serve the entire family in one quick, convenient visit. While there are many common business like bicycle rental like, Tuck-'n' -Roll will excel due to its attention to detail regarding customer service. Through unheralded customer attention, Tuck' n'-Roll will slowly but surely gain market share as it services the entire family, creating long-term relationships. Furthermore, Tuck-'n'-Roll location will allow it to attract a lot of walk in traffic. We, Tuck-'n'-Roll, saw the opportunity that this business has the potential of success provided that it is handled efficiently. We want to promote this extreme sport is safe and able to be joined by amateur or athletes, especially for family activities in the weekend. Consequences, creates a healthy lifestyles among Malaysian. Tuck-'n'-Roll sees this as a way to prosper in this market, by taking advantage of all these people's need.